Dinâmica hidrogeomorfológica e cenários sazonais em nascentes do rio São Francisco, na Serra da Canastra, Minas Gerais - Silva, Giliander Allan da (2019)
The springs make up the initial part of the hydrological cycle on the surface. They represent the contact of groundwater and subsurface with the outside of the lithosphere, initiating the channels that form the drainage network. The study was carried out in seven springs in the Chapadão Diamante, in Serra da Canastra, Minas Gerais, whose morphological characteristics constitute it as a "drainage diverter" and, therefore, harbor innumerous large springs that originate rivers of national and regional importance . In mountainous areas it is common for cover materials to be shallow, which makes springs more sensitive to small changes in rainfall. Although they have important characteristics, they do not perceive deserved attention to the areas of beginning of the drainage channels, which are lacking studies in the national scenario. The dynamics of the springs studied come from pluviometric features and local lithostructure, which conditions surface materials, relief microforms in headwaters and vegetation cover, but are also strongly influenced by the existence of roads and maintenance activities. In this way, we aim to characterize the springs studied based on the hydrogeomorphological processes involved, be they natural and / or anthropic. The sources were distinguished according to the origin of the source, flow, morphology, types of exfiltration, seasonality (constant or intermittent activity) and spring mobility. Mapping followed by ultra-detail relief modeling was performed by RPAs in order to identify the headform microforms and their function in the infiltration dynamics. The uncooled materials were characterized by their granulometry. The lithology has a great contribution to the hydrogeomorphological dynamics of the sources studied. Of the seven springs, six were characterized as intermittent and one as perennial. The thin layer of the unconsolidated material that is conditioned by the resistance of the quartzitic rock, implies a lower retention of water from the rain, triggering the rapid flow of water to the reef, resulting in low contribution of the base stream to the perenniality of the drainage system. The areas with higher water infiltration and retention conditions are linked to the deposition pockets. These tend to occur mainly in headwaters with SE-NO alignment, by the direction and dip of the arched layers in the period of metamorphism, which provide a bus to the transport of the coluvial material.